IMPROVING STUDENT’S SPEAKING ACHIEVEMENT THROUGH SIX THINKING HAT STRATEGY AT SMA NEGERI 11 PALEMBANG - Rizki Larasanti; Rahma Dianti (Jurnal Didascein Bahasa, 2019)
This study aimed for investigating: (1) whether or not Six Thinking Hat strategy significantly improved student’s speaking achievement, and (2) whether or not there was any significant difference in students’ speaking achievement between those who were taught by using Six Thinking Hats strategy and those who were not. A quasi experimental research design was administered. The samples were taken by using purposive sampling, consisting of 34 students for experimental group and 29 students for control group. Spoken test was used as data collection technique. To verify the hypotheses, the data from the pre-test and post-test from the two groups were analyzed by paired sample t-tst and independent sample t-test. Based on the results of the study, it was revealed that Six Thinking Hats strategy could significantly improve students’ speaking achievement. The result of paired sample t -test confirmed that there was a significant progress of students’ speaking achievement in giving opinion after they got the intervention of this strategy. Next, the result of Independent-sample t-test showed that there was a significant difference between students’ speaking achievement for both of groups. Experimental group outperformed control group in speaking achievement